EXPERIMENTAL ANALYSIS OF A HYBRID DRYER - Ferreira, A. G.; Charbel, A. L. T.; Pires, R. L.; Silva, J. G.; Maia, C. B. (Revista de Engenharia Térmica, 2007)
Artificial dryers promote a high-quality food drying, in spite of the considerable energy consumption. Solar dryers use only solar energy to heat the drying airflow; nevertheless, it is not possible to control the airflow thermal conditions. Hybrid solar dryers arise as an interesting option to reduce the drying costs (compared to the artificial dryer’s costs). Hybrid solar dryers improve the quality of the final product due to the control of the thermal drying condition. This paper presents an experimental analysis of an innovative hybrid solar-electrical dryer. This dryer consists of two chambers: solar chamber and drying chamber with electrical air heater. An experimental evaluation of the airflow in the device was performed and the average values of the temperature and the mass flow were presented as a function of the ambient conditions. To determine the performance of the proposed dryer, banana slices were dried in the device and the results were compared with natural sun drying and artificial drying.